NUEVA ESPIRITUALIDAD: UN ANÁLISIS SOBRE LA LIMINALIDAD Y EL PERSONAJE DE LA COYOTA DEL RELATO “AVENTURA EN BETHANIA” DE RAMÓN J. SENDER. - Ducha Martínez, Leyre (ConSecuencias, 2024)
This study focuses on Ramón J. Sender’s exile-era short fiction, with particular attention to the aesthetic dimension of Aventura en Bethania, a story included in the anthology Novelas ejemplares de Cíbola (1961). This volume—born out of the Aragonese writer’s cultural integration into the American Southwest—has often been examined in relation to his earlier work Mexicayotl, published shortly after Sender arrived in Mexico following the Spanish Civil War. However, the present piece argues for the autonomy of the 1960s anthology, highlighting the interaction of European-origin characters with traditional symbols deeply rooted in universal history and persisting into modern times.Drawing on a theoretical framework that connects the human axiological dimension with the crystallization of seriocomic genres and their influence on longer forms such as the novella, this study underscores the uniqueness of Aventura en Bethania as a menippean satire, in contrast to the other texts in the collection, which are likewise shaped by a seriocomic impetus. To this end, it engages the aesthetic worldview proposed by Professor Luis Beltrán (University of Zaragoza), along with contributions from Marta Añorbe (2023) and Mikhail Bakhtin, whose fourteen defining features of Menippean satire prove crucial to the analysis. Este trabajo se centra en la cuentística del exilio de Ramón J. Sender, con especial atención a la dimensión estética de Aventura en Bethania, relato incluido en la antología Novelas ejemplares de Cíbola (1961). Este volumen, fruto de la integración cultural del autor aragonés en el suroeste de Estados Unidos, se ha estudiado a menudo en relación con su precedente narrativo, Mexicayotl, publicado poco después de la llegada de Sender a México tras la Guerra Civil española. No obstante, aquí se reivindica la autonomía de la antología de los años sesenta, subrayando la interacción de personajes europeos con símbolos tradicionales que hunden sus raíces en la historia universal y perviven hasta la Modernidad. El artículo adopta un marco teórico que vincula la dimensión axiológica del ser humano con la cristalización de los géneros seriocómicos y su influencia en formas mayores como la novela corta. A su vez, defiende la singularidad de Aventura en Bethania como una sátira menipea, en contraste con el resto de la colección, que también comparte este influjo seriocómico. Para ello, se recurre a la cosmovisión estética propuesta por el profesor Luis Beltrán (Universidad de Zaragoza), junto con los aportes de Marta Añorbe (2023) y Mijaíl Bajtín, cuyas catorce características de la sátira menipea resultan fundamentales para el análisis.